The Relationship of Learning Concentration with Children's Learning Activities in PAUD Qatrinnada Padang - Lawati, Susi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
Early children educations are one form of education that focuses on laying a foundation towards grown and physical development, intelligence, social-emotional, languages and communication according to tho the uniqueness and stage of development that is passed by early childhood. Early children's education basically covers all the efforts take it by educator and parents in the process to get care, and education for children with creat an environment of children can explore experiences that provide opportunities for them to recognize and understand the learning experient they have gained from the environment. Through observing, imitating, and experimenting which takes places repeated and increases the full the children's potentials and intelligence.Keywords: Activities, Concentration, Communication